Structured Electronics Design A Conceptual Approach to Amplifier Design, 3rd ed. - J.M. Montagne, Anton (TU Delft Open, 2023)
Many people consider analog electronic circuit design complex. This is because designers can achieve the desired performance of a circuit in many ways. Together, theoretical concepts, circuit topologies, electronic devices, their operating conditions, and the system's physical construction constitute an enormous design space in which it is easy to get lost. For this reason, analog electronics often is regarded as an art rather than a solid discipline. Structured Electronics Design: Defines a step-by-step hierarchically organized design process. Is based on solid principles from systems engineering, physics, signal processing, control theory, and network theory. Provides a solid foundation for circuit design education and automation. Has been developed at the TU Delft since the 1980s.